Bacterial expression systems based on Tymovirus-like particles for the presentation of vaccine antigens - Ogrina, Anete; Balke, Ina; Kalnciema, Ieva; Skrastina, Dace; Jansons, Juris; Bachmann, Martin F.; Zeltins, Andris (Frontiers in Microbiology, 2023)
Virus-like particles (VLPs) are virus-derived artificial nanostructures that resemble a native virus-stimulating immune system through highly repetitive surface structures. Improved safety profiles, flexibility in vaccine construction, and the ease of VLP production and purification have highlighted VLPs as attractive candidates for universal vaccine platform generation, although exploration of different types of expression systems for their development is needed. Here, we demonstrate the construction of several simple Escherichia coli (E. coli) expression systems for the generation of eggplant mosaic virus (EMV) VLP–derived vaccines. We used different principles of antigen incorporation, including direct fusion of EMV coat protein (CP) with major cat allergen Feld1, coexpression of antigen containing and unmodified (mosaic) EMV CPs, and two coexpression variants of EMV VLPs and antigen using synthetic zipper pair 18/17 (SYNZIP 18/17) and coiled–coil forming peptides E and K (Ecoil/Kcoil). Recombinant Fel d 1 chemically coupled to EMV VLPs was included as control experiments. All EMV – Feld1 variants were expressed in E. coli, formed tymovirus–like VLPs, and were used for immunological evaluation in healthy mice. The immunogenicity of these newly developed vaccine candidates demonstrated high titers of Feld1-specific Ab production; however, a comparably high immune response against carrier EMV was also observed. Antibody avidity tests revealed very specific Ab production (more than 50% specificity) for four out of the five vaccine candidates. Native Feld1 recognition and subclass-specific antibody tests suggested that the EMV-SZ18/17–Feld1 complex and chemically coupled EMV–Feld1 vaccines may possess characteristics for further development.